Bully Comments Classification on TikTok Using Support Vector Machine and Chi-Square Feature Selection - Putri, Amelia; Abdiansyah, Abdiansyah; Utami, Alvi Syahrini (Sriwijaya Journal of Informatics and Applications, 2024)
TikTok has been named the world’s most popular social media platform. The high level of TikTok use makes it easier for an irresponsible user to do unethical things such as spreading hateful comments on someone’s account. TikTok developers can prevent bullying by using policies such as word detection and filtering features that indicate comments fall under the category of bullying or non-bullying comments. Therefore, we conducted this study to classify bullying comments using Machine Learning methods for convenience purposes on TikTok usage, a method that we used in this research is the SVM method to classify the data and Chi-Square as the feature selection. Tests were carried out using the Linear, Polynomial, and RBF kernel functions with the C parameter, namely 0,1, 1, and 10 for each kernel. The results of this research show that the Support Vector Machine method with Chi-Square Feature Selection has a better performance.  This was proven by the increased accuracy in RBF kernel C=0,1 which was 0,20